PENCEGAHAN PENYEBARAN INFEKSI DAN PENGGUNAAN TELEDENTISTRY SELAMA PANDEMI COVID-19 - Nyoman Ayu Anggayanti; Putu Lestari Sudirman; Putu Fenti Surya Pratami; Dewi Anggraini (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: COVID-19 is a new virus that was first discovered in Wuhan, China. In mid-2020, the number of deaths continued to increase worldwide. Topics: Dentist are professions that are susceptible to infection, so they must implement preventive measures and apply alert behavior to all patients. Discussion: The American Dental Association (ADA) describes teledentistry as "the use of telehealth systems and methodologies in dentistry", which includes "a wide variety of technologies and practices to provide virtual medical, healthcare, and educational services. Conclusion: Prevention of disease transmission by using complete personal protective equipment, selection of emergency cases and teledentistry can be carried out during the COVID-19 pandemic to reduce the possibility of transmission at the dentist's practice.